2019
DOI: 10.1002/jgh3.12292
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of isolated gastric varices in liver cirrhotic patients: A single‐referral‐centre retrospective cohort study

Abstract: Introduction Gastric varices (GVs) occur in 10–30% of liver cirrhotic patients, with a mortality rate of up to 45%. Rupture of isolated GVs (IGVs) is less prevalent but often results in more severe hemorrhage and a higher risk of mortality than rupture of esophageal varices (EVs). However, there is no clear consensus yet about the optimal management for incidentally discovered IGVs. Objective To determine the clinical significance of IGVs in liver cirrhotic patients. Methods This was a retrospective cohort end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…CP class C was the only one found to be a risk factor for 1-year mortality in cirrhotic patients through multivariate analysis (HR, 26.77; 95% CI, 6.01-119.34; P =0.001). 72 Consistent with the previous study, the presence of high-risk varices was 80.60% in patients with CP class C, significantly higher compared to patients with CP class A (47.50%). EVL was done in 46.7% of patients; 33.6% of EVL during screening of varices, 39% after evaluation of previous EVL, and 27.4% due to AVB.…”
Section: Managing Egv In Clinical Practicesupporting
confidence: 91%
See 2 more Smart Citations
“…CP class C was the only one found to be a risk factor for 1-year mortality in cirrhotic patients through multivariate analysis (HR, 26.77; 95% CI, 6.01-119.34; P =0.001). 72 Consistent with the previous study, the presence of high-risk varices was 80.60% in patients with CP class C, significantly higher compared to patients with CP class A (47.50%). EVL was done in 46.7% of patients; 33.6% of EVL during screening of varices, 39% after evaluation of previous EVL, and 27.4% due to AVB.…”
Section: Managing Egv In Clinical Practicesupporting
confidence: 91%
“…The use of platelet count/ bipolar spleen diameter ratio for detection of high-risk varices in compensated cirrhotic patients had area under the receiver operating characteristic curve of 0.77, sensitivity of 90.6%, and specificity of 58.3%. 74 A recent study by Lesmana et al 72 showed that EV was found in 73.20% of LC patients; meanwhile GOV and IGV were only found in 18.30% and 8.49%, respectively. Although GV is less prevalent than EV, patients with GV, particularly GOV, were associated with a greater risk for AVB.…”
Section: Managing Egv In Clinical Practicementioning
confidence: 97%
See 1 more Smart Citation
“…5,6 Gastric Varices have a poorer prognosis, as they result in a much heavier blood loss and a higher bleeding and thus higher mortalityrate. 4,7 In a large study which included 568 patients, initial endoscopy showed gastric varices in 20% of patients and 9% of patients developed gastric varices over a mean follow up of 24.6 ± 5.3 months, however, this was after eradication of esophageal varices and a mortality of 45% was reported. 5 Contrary to this a recent study reported the 6 weeks mortality of GV bleeding to be only 16.7%.…”
Section: Introductionmentioning
confidence: 99%